Isatuximab for the treatment of relapsed/refractory multiple myeloma - Richardson, Paul G; Beksaç, Meral; Špička, Ivan; Mikhael, Joseph (Expert opinion on biological therapy, 2020)
INTRODUCTION: Although new drug classes have significantly extended survival of patients with multiple myeloma, they continue to experience multiple relapses and/or become refractory to treatment. Therefore, novel therapies and treatment combinations with different mechanisms of action are needed to improve the outcomes of patients with relapsed/refractory multiple myeloma. AREAS COVERED: Here, the authors review the published data regarding the development and clinical investigation of isatuximab, a CD38 monoclonal antibody, for treatment of patients with relapsed/refractory multiple myeloma. The mechanisms of action, clinical efficacy, and safety of isatuximab treatment are summarized. EXPERT OPINION: Isatuximab is approved in combination with pomalidomide/dexamethasone for the treatment of adults with relapsed/refractory multiple myeloma who have received at least two prior therapies, including lenalidomide and a proteasome inhibitor. Isatuximab displays a manageable safety profile, with infusion reactions being the most common adverse events. Isatuximab is currently being further evaluated in combination with other backbone regimens in relapsed/refractory and newly diagnosed multiple myeloma.
Keywords: výsledek terapie; Recurrence; CD38; lokální recidiva nádoru; Antineoplastic Combined Chemotherapy Protocols; Antineoplastic Agents, Immunological; multiple myeloma; chemorezistence; Adult; dospělí; Multiple Myeloma; monoclonal antibody; protinádorové látky imunologicky aktivní; recidiva; relapsed/refractory; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; isatuximab; Neoplasm Recurrence, Local; lidé; Humans; protokoly protinádorové kombinované chemoterapie; lenalidomid; Drug Resistance, Neoplasm; mnohočetný myelom; Lenalidomide